A Cultural Exploration of Balinese Woven Borders (Tenunan Pinggiran Saput Bali) - STEELYANA, Evy W; WAWORUNTU, Mariah; WAWORUNTU, Ine (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:This paper explores the intricate relationship between Balinese woven borders, known as "pinggiran Saput," and their cultural significance within the broader context of Balinese heritage. The study delves into the historical evolution of weaving techniques and materials, highlighting the transition from traditional hand-spun cotton and natural dyes to modern synthetic fibers, reflecting innovation and cultural continuity.Methodology:Next, the paper examines the symbolism embedded in the patterns and colors of these textiles, illustrating how they convey narratives of spirituality and identity. It also discusses the impact of globalization on the preservation of these traditional crafts, highlighting the economic challenges local artisans face due to the influx of cheaper, mass-produced alternatives.Findings:The findings suggest that effective strategies for promoting authentic Balinese craftsmanship and fostering consumer awareness are essential for sustaining the cultural legacy of Balinese woven borders.Implication:Ultimately, this research underscores the importance of these textiles not only as decorative elements but as vital expressions of community identity and cultural resilience in the face of modern challenges.